Analisis Pengaruh Corporate Governance dan Kualitas Audit terhadap Integritas Laporan Keuangan pada Perusahaan Manufaktur Sub Sektor Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia Periode 2012-2017 - Ambar Purwantiningsih; Desy Anggaeni (Penerbit Goodwood, 2021)
Purpose: The integrity of financial statements is the correctness of the information contained in financial statements that describe the actual condition of the company. This study examined the influence of Corporate Governance, which was proxied by Institutional Ownership, Managerial Ownership, Independent Commissioners, Audit Committees and the effect of Audit Quality on the Integrity of Financial Statements. Research methodology: The population in this study were 13 Manufacturing and Automotive Sub Sector Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2012-2017 period. The sample selection technique used was purposive sampling and obtained six companies that met the researcher's criteria. The data analysis method used in this study is multiple linear regression analysis using SPSS version 25.0 for windows. Results: The results show that institutional ownership, managerial ownership, independent commissioners, and audit quality have a positive and significant effect on the integrity of financial statements, while the audit committee has no effect on the integrity of financial statements.